Reproductive Health Status of Married Women Participating In Cervical Cancer Screening In Kathmandu - Sherpa, Ang Tshering; Singh, Neeti; Bajracharya, Manisha; Pradhan, Amita; Pradhan, Peru (Journal of Chitwan Medical College, 2019)
Background: Reproductive health of women has been the central agenda of Cairo conference since its inception in 1999. As a signatory country for Cairo Conference, Nepal government is also committed for reproductive rights for Nepalese women. Despite this, reproductive health challenges do exist in Nepal. This prompted us to determine the reproductive health status of married women attending in cervical cancer screening in Kathmandu. Methods: Cross sectional study was designed to include retrospective data of married women, obtained during cervical cancer screening camp conducted by KIST Medical College at Laga Khala Clinic, Lagan, Kathmandu on 12-02- 2017. Among married women (131) attended cervical 100 women’s records with complete set of data for reproductive health variables required for the study were included in this study. Statistical analysis was done descriptively. Results: Participant’s age is between 21 years to 61 years, 83% are literate and 46% are employed. Adolescence marriage and pregnancy were two main problems noted. Cervical examination in relation showed 3% (3) VIA positive, 33% (33) Cervicitis, 10% (10) cervical polyp, 7% (7) atrophic vaginitis, 4% (4) cervical erosion and 43% (43) healthy cervix. Regarding Knowledge about risk factor majority 92% (92) had either no knowledge or only some extent of knowledge. Conclusions: Married women who lives in Kathmandu has significant reproductive health problem. Urban health program should address these issues.